Major obstetric haemorrhage of 2000 ml or greater: a clinical audit. (17th November 2018) - O'Sullivan, J.; Mansfield, R.; Talbot, R.; Cairns, A. E.
Abstract: Haemorrhage remains a leading cause of maternal death. We conducted an audit to identify strategies to improve the management at our local NHS Trust. A data collection form was based on our local guideline. A coded database search was conducted for all deliveries where the estimated blood loss was ≥2000 ml (from June 1 2015 to December 31 2015), returning 68 search results (13.7/1000 births). Fifty-six records were included. Poor compliance (<75%) was seen in some key areas including the major obstetric haemorrhage (MOH) call activation (52%), the presence of an anaesthetic consultant (63%) and tranexamic acid administration (46%). Thirty out of 56 cases (54%) were acutely transfused. Women, who were not transfused acutely, appeared to be more likely to need a secondary transfusion if no MOH call had been activated (9/27 (33%) versus 3/29 (10%), p  = .052). A key area for improvement was the activation of MOH calls. Following this audit, we adjusted our guideline to make it more clinically useful and staff training sessions were held, including simulation training. Impact statement: What is already known on this subject? A postpartum haemorrhage (PPH) is an obstetric emergency. A structured approach is important to optimise the care of the mothers during this dangerous time, and has been shown to reduce the transfusion requirements. However, clinical practice may not adhere to the guideline recommendations. What the results of this study add? With the objective evidence of increased rates of PPH ≥2000 ml at our institution, our work identifying the flaws in management was a critical component of the work to improve the outcomes. This study gives impetus to find innovative ways to improve adherence to guidelines, and inspired an update of our local guideline to improve the applicability and utility. This project suggests a new marker for the adequacy of an acute management (a requirement for secondary blood transfusion without having received an acute transfusion), and raises questions about what constitutes optimum PPH management. What the implications are of these findings for clinical practice and/or further research? The primary and secondary transfusion data raised new questions to investigate in the future: does the involvement of consultants and the escalation of care via the instigation of major haemorrhage protocols improve decision-making and patient outcomes? Does the necessity for a secondary transfusion indicate a suboptimal acute care?